Improving Vocabulary Mastery of the Seventh Grade Students of Smp Negeri 1 Sindue Tobata Through Cartoon Movie - Rachmawati, Redzky; Dewi, Anjar Kusuma; Lebagi, Desrin; Marhum, Mochtar (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improving vocabulary mastery of the seventh grade students through cartoon movie at SMP Negeri 1 Sindue Tobata. This research used a quasi-experimental research design. The population of this study consisted of 67 students from class VII A, VII B, and VII C at SMP Negeri 1 sindue tobata. The sample was class VII C, as the experimental group, and class VII B, as the control group. This study used simple purposive sampling. The researcher administered pretests and posttests during data collection. The results showed that the mean score of the experimental group on the post-test (75) was higher than that of the control group (50). This was confirmed by calculations using the SPSS 26 version, where The significance value (Asymp. 2-tailed) is 0.000, which is smaller than the significance of 0.05; this indicates that the alternative hypothesis (Ha) is accepted. These findings suggest that through cartoon movies are an effective medium for improving students’ vocabulary mastery in English language teaching.